PREVALENCE OF NEAR MISS AND MATERNAL DEATHS AND ITS MATERNAL AND PERINATAL OUTCOMES: A RETROSPECTIVE STUDY - MADAN, ANITA; SHARMA, PALLAVI; KAUR, JAGDEEP; PURI, ANISHA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The objective of the study was to determine maternal mortality ratio (MMR), maternal near miss incidence ratio (MNM IR), MNM to mortality ratio (MNM: MD), and mortality index (MI) and to know the prevalence, demographic distribution, causes and feto-maternal outcome of maternal near miss and maternal deaths. Methods: A retrospective review of near miss and maternal mortality over a period of 20 months in a tertiary teaching hospital in Punjab. Results: MMR was 998 MNM IR was 24.20/1000 live births. Maternal near miss mortality ratio was 2.4:1. MI was 29.21%. The most common cause of maternal mortality was hypertension, which was seen in 14 (53.84%) women. Among near miss cases, the most common complication noted was hemorrhage, seen in 40 (63.49%) cases. Among maternal deaths, 7 (26.92%) women delivered vaginally, 6 (23.07%) women underwent emergency cesarean section. Among near miss cases, 20 (31.74%) women delivered vaginally, 13 (20.63%) women underwent cesarean section while 7 (11.11%) had cesarean hysterectomy. Laparotomy for ruptured ectopic pregnancy was done in 6 (9.52%) women, 7 (11.11%) women had dilatation and evacuation, 3 (4.76%) had exploration of Uterovaginal canal. Preterm birth has seen in 8 (12.69%) in maternal deaths and 23(36.50%) in maternal near miss. Intrauterine fetal demise occurred in 4 (6.34%) in maternal deaths and 2 (4.87%) in near miss. Conclusion: The review of near miss cases is important to identify response of health care system to medical emergencies and provides opportunities to improve the quality of service.